Age at Diagnosis and Baseline Myelomalacia Sign Predict Functional Outcome After Spinal Meningioma Surgery - Wach, Johannes; Banat, Mohammed; Schuss, Patrick; Güresir, Erdem; Vatter, Hartmut; Scorzin, Jasmin (Frontiers in Surgery, 2021)
Objective: Spinal meningioma (SM) accounts for 12% of all meningiomas. Clinical and immunohistochemical factors were analyzed with regard to functional outcome, surgical adverse events, and tumor recurrence. Methods: One-hundred and twenty-three consecutive SM patients underwent surgery and were retrospectively reviewed with regard to demographic parameters, imaging features, neurological function, and immunohistochemical items. Neurological function was graded according to the Modified McCormick Scale (MMS) and dichotomized as “good (grade I+II)” and “poor (grade III–V)” function. Results: One-hundred and fourteen (92.7%) WHO grade I and 9 (7.3%) WHO grade II SM were included in this study. Univariate analysis identified a baseline T2 hyperintensity of the spinal cord, baseline symptom duration ≥4 weeks, age ≥66 years, and dural tail sign as predictors of poor MMS. Baseline T2 hyperintensity of the spinal cord (Odds ratio (OR) =13.3, 95%CI=3.4-52.1, p<0.001) and age ≥66 years (OR=10.3, 95%CI=2.6-41.1, p=0.001) were independent predictors of a poor MMS grade at discharge after SM surgery in the multivariate binary logistic regression analysis. Univariate cox regression analysis revealed that WHO grade II, cervical location, ventral tumor attachment, male sex, dural tail sign, Simpson grade (III+IV), and MIB-1 index ≥ 5% were associated with an increased risk of tumor recurrence. Multivariate cox regression analysis showed that MIB-1 labeling index ≥5% is an independent risk factor for tumor recurrence (Hazard ratio=1.77, 95%CI=1.01-3.11, p=0.047). Conclusion: Baseline T2 hyperintensity, especially in the elderly patients, is a strong predictor of poorer recovery after spinal meningioma surgery. SMs with high proliferative activity should be followed-up closely despite maximal safe resection.